Watch out for a revival of peginesatide in sports. Issue 2 (9th June 2016) - Jelkmann, Wolfgang
Abstract : The erythropoietin‐mimetic peptide (EMP) peginesatide belongs to the group of erythropoiesis‐stimulating agents (ESAs) that are prohibited when misused in sports. Peginesatide is a synthetic pegylated homodimer of two cyclic 21‐amino acid chains. It was approved for the treatment of anaemic patients with chronic kidney disease in the USA in 2012, but recalled in 2013 due to prevalent cases of acute severe anaphylactoid reactions and associated fatalities (0.02%). The drug was considered obsolete for athletes and part of the anti‐doping scene lost sight of it. However, recent research indicates that the adverse events were not caused by the drug substance, but by the drug product formulated in multi‐use vials. These vials contained comparably high levels of subvisible particles. Phenol was identified as a critical component of the drug formulation, which caused the release of histamine from mast cells. Tricky athletes might consider peginesatide a pharmacologically safe ESA in an appropriate formulation. In addition, other EMPs may get a second wind for therapy including misuse in sports. Therefore, it is very important to proceed in developing electrophoretic, immunological, and mass spectroscopic methods for detecting peginesatide and other EMPs in human urine and blood samples. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The marketing of the erythropoietin‐mimetic drug peginesatide was stopped in 2013 due to serious hypersensitivity reactions. However, clinical interest in peginesatide has been rekindled by recent studies showing that the adverse drug reactions were anaphylactoid and probably not caused by the drug substance, but by the formulated drug product. The possibility of having a safe erythropoiesis‐stimulating drug cheaper than recombinant erythropoiesis‐stimulating agents implies a strong potential for penetration of the sport doping market.